Trendy or topical? Sexual politics and panopticism in the 2016 BBC Midsummer Night's Dream. Issue 1 (July 2019) - Földváry, Kinga
The 2016 BBC television production of A Midsummer Night's Dream (directed by David Kerr) illustrates that the provocative representation of gender issues, commented on by most reviewers, effectively overshadowed the film's real topicality: its depiction of a tightly controlling post-panoptic regime, relying on technological surveillance systems, in which observed and observer are equally implicated. However, the film's spectacular visuality and the liberal gender politics of the adaptation, which are all but compulsory in contemporary theatrical adaptations, have allowed viewers to focus on the carnivalesque comedy of the finale, rather than the darker undertones of its social criticism.